Tax Assistance for Article 21 Income Tax and Corporate Income Tax at PT Gravitas Indonesia Maju - Alek Murtin; Erni Suryandari Fathmaningrum; Icha Latifa Chandra; Muhamad Rifandi (ASIAN PUBLISHER, 2026)
State revenue sources come from various aspects. In Indonesia, taxes are the main source of income for the state, both from personal and corporate taxes and will be used for the benefit of the state. Most of the state's needs include financing building projects, employee expenses, construction of public facilities and other needs come from taxes. Factors that influence taxpayer compliance consist of internal factors are factors that arise from the taxpayer itself, for example the understanding and perception of tax rates from taxpayers, external factors are factors that arise from outside the taxpayer, for example the standard of service or quality of officers in serving taxpayers and tax socialization carried out by the Directorate General of Taxes with the aim of creating taxpayer compliance regarding corporate income tax and article 21 income tax. Income Tax or PPh is a tax imposed on every individual or corporate taxpayer regarding the income received or obtained in the tax year. Article 21 Income Tax (PPh) is a tax imposed on income in the form of salaries, wages, honorariums, allowances, and other payments in any name and form in connection with work, services, or activities carried out by individual taxpayers within the country. Income Recipients (Tax Subjects) are domestic individuals, such as permanent employees, temporary employees, pension recipients, former employees, and activity participants. Income Providers (Tax Withholding Agencies) are usually companies or agencies that are required to withhold Article 21 Income Tax when paying income to recipients.